The cost of fear of crime on apartment prices - Vania Ceccato; Mats Wilhemson (European Regional Science Association (ERSA), 2010)
Evidence shows that crime affects housing prices. However, whether fear of crime impacts equally on prices of properties is an issue little investigated in the international literature. In this article we assess the impact of perceived safety on housing prices in the city of Stockholm, capital of Sweden. The study uses data over apartment sales and responses of 2008's Stockholm Safety Survey aggregated by parishes. The effect of perceived safety is assessed using hedonic pricing modelling controlling for a number of land use covariates using Geographical Information System (GIS). The paper finalises with a discussion of the key findings of study.
Keywords: 330; fear of crime; housing prices; hedonic modelling; GIS